Exploring Teachers’ Experiences of Inclusion Strategies for Deaf Children in Mainstream Primary Schools - Cunneen, Holly (STER, 2019)
This study aims to highlight the strategies used to meet the needs of the deaf children in their class. By doing so, teachers’ competencies in teaching deaf children in mainstream schools, alongside their views of the possible link between a deaf child’s level of hearing and their level of inclusion in the mainstream class will be briefly discussed. From this investigation, it was found that there are whole class benefits to using inclusion strategies for deaf children. The lack of Continuing Professional Development (CPD) and insight into deaf education in initial teacher education and a relationship between a deaf child’s level of hearing and their level of inclusion they experience in mainstream classes also came to light.
Journal article
Keywords: Research Subject Categories::SOCIAL SCIENCES; Special Education; Inclusion; Hearing Impairment; Primary Education; STER